Durable consumption, limited VAT pass-through and stabilization effects of temporary VAT changes - Marius Clemens; Werner Röger (Deutsches Institut für Wirtschaftsforschung (DIW), 2022)
This paper revives the question of whether a temporary VAT change is an adequate instrument for crisis stabilization. In empirical assessments, we find that durable goods consumption fluctuates strongly over the business cycle and that VAT rate changes affect durable goods in particular. Therefore, we build a dynamic stochastic general equilibrium (DSGE) model that is capable of addressing this major channel through which temporary VAT changes affect the economy. Furthermore, we allow for an imperfect pass-through of VAT measures to consumer prices via VAT-specific price adjustment costs. We compare the general VAT policy in the crisis with alternative stabilization policies, such as interest rate cuts, spending policies and a VAT cut only for durable goods. First, we find that considering durable goods in the model generates sizeable stabilization effects of VAT changes on consumption over a broad set of parameter ranges. Second, we find that the VAT policy can mimic monetary policy with minor exceptions. Third, the VAT rate cut has the highest short-term multiplier compared with government spending policies, but not in the medium-term. Fourth, a VAT rate reduction only on durable goods will generate strong GDP effects and even be self-financing in the first year. In contrast, a VAT reduction only on non-durables has small effects on GDP and is not self-financing. In view of our results, we conclude that a temporary VAT cut, when applied to durable goods, is an effective stabilization instrument.
Keywords: E62; E63; H21; 330; Value added tax; durable consumption; multiplier; business cycle; zero lower bound